Model Simulasi Pengaruh Investasi Keberlanjutan terhadap Penguatan Industrialisasi di Wilayah Kota Surabaya - Ananda Afifan Efendi; Rachel Sandria Ivana; Muhamad Yasin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The shift in the industrial development paradigm towards a sustainable concept has necessitated the development of investment models that are not only oriented towards economic growth but also consider aspects of resource efficiency, technological innovation, and environmental sustainability. This study aims to analyze the relationship model between sustainable investment and industrialization strengthening in the context of urban development using a simulation approach in the city of Surabaya. The research method used is a simulation-based quantitative approach to examine the relationship patterns between variables based on a conceptual model developed from the theory of sustainable industrialization. The research data uses a simulation dataset compiled based on indicators of sustainable investment and industrialization strengthening, so the results do not represent actual empirical conditions, but rather describe the relationship scenario between variables. Data analysis was conducted using descriptive statistics and linear regression through testing the regression coefficient, model significance, and coefficient of determination (R²). The simulation results indicate that sustainable investment has a positive relationship with industrialization strengthening in the developed model. Increasing aspects of green investment, technological innovation, and resource efficiency have the potential to be supporting factors in strengthening the capacity of regional industrialization. This study provides a conceptual contribution to the development of sustainable industrialization studies and provides an initial modeling basis for further empirical research using actual data. The implications of this research demonstrate the importance of integrating sustainability principles into investment strategies to support a more adaptive and sustainable urban industrial transformation.